Spinoza's radical Cartesian mind - Nyden-Bullock, Tammy (Continuum studies in philosophy., 2007)
'Spinoza's Radical Cartesian Mind' blends historical analysis, intellectual history and philosophical analysis to create a work which will be of value to Spinoza scholars, historians, philosophers and students of intellectual history.